Legal Framework for Prosecution of Sexual Violence Cases in Bosnia (Journal of Social Sciences Review, 2022)
International tribunals have been very important in bringing criminals to justice involved in sexual violence. The tribunal has demonstrated that it is possible to effectively prosecute wartime sexual violence and has provided a forum for unfortunate victims to discuss their suffering. The tribunal is anticipated to be capable of prosecuting and exploring a variety of international and domestic sexual abuse. The legal framework and various laws that have been implemented to it have improved the regulatory and legal structure for the prosecution of national war crimes, which has led to a decrease in the various crimes of sexual violence on a worldwide scale. The article that follows is based on qualitative methods of research. An analysis of qualitative research methodology is presented in the following article.
Keywords: Cases in Bosnia; Sexual Violence; Legal Framework; Prosecution of Sexual Violence